2012
DOI: 10.1242/jeb.064832
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation strategies to seasonal changes in environmental conditions of a domesticated horse breed, the Shetland pony (Equus ferus caballus)

Abstract: SUMMARYRecent results suggest that the wild ancestor of the horse, the Przewalski horse, exhibits signs of a hypometabolism. However, there are speculations that domestic animals lost the ability to reduce energy expenditure during food shortage and adverse environmental conditions. Therefore, we investigated physiological and behavioural strategies employed by a robust domesticated horse breed, the Shetland pony, over the course of a year under temperate conditions by measuring ambient temperature (T a ), sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
63
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 52 publications
6
63
1
2
Order By: Relevance
“…Interestingly, our results did not reveal any difference in the mean daily T v between summer and winter. However, the results of a previous study on subcutaneous temperature in the same animals showed distinct nocturnal reductions in subcutaneous temperature that were greater in food-restricted animals compared with animals fed ad libitum (Brinkmann et al, 2012). Studies in humans showed that acclimated indigenous people have the ability to slightly reduce their metabolism during cold nights by allowing intensive peripheral cooling and a slight reduction in body core temperature (Scholander et al, 1958;Hammel et al, 1959) while unacclimated non-indigenous people showed a decrease in skin 111815 temperature in combination with an erratic increase in nocturnal metabolic rate by shivering.…”
Section: Research Articlementioning
confidence: 66%
See 1 more Smart Citation
“…Interestingly, our results did not reveal any difference in the mean daily T v between summer and winter. However, the results of a previous study on subcutaneous temperature in the same animals showed distinct nocturnal reductions in subcutaneous temperature that were greater in food-restricted animals compared with animals fed ad libitum (Brinkmann et al, 2012). Studies in humans showed that acclimated indigenous people have the ability to slightly reduce their metabolism during cold nights by allowing intensive peripheral cooling and a slight reduction in body core temperature (Scholander et al, 1958;Hammel et al, 1959) while unacclimated non-indigenous people showed a decrease in skin 111815 temperature in combination with an erratic increase in nocturnal metabolic rate by shivering.…”
Section: Research Articlementioning
confidence: 66%
“…It has been postulated that these pronounced seasonal fluctuations in MR are based on a reduction in physical activity and the heat increment of feeding and are not dependent on any reduction of BMR (Mautz et al, 1992;Mesteig et al, 2000). However, studies on red deer (C. elaphus), Alpine ibex (Capra ibex ibex), Przewalski horses (Equus przewalski) and domesticated horses (Equus caballus) revealed a nocturnal hypometabolism that contributes to reduced energy expenditure in late winter when food availability is low (Arnold et al, 2004;Kuntz et al, 2006;Signer et al, 2011;Brinkmann et al, 2012). In these last studies, the assumption of a reduced MR as an adaptation strategy to food shortage and low T a was based on the measurement of activity, heart rate and T b or subcutaneous temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Reducing energy intake to about 70% of maintenance energy requirements decreased the body core temperature of sheep (Ovis aries) by about 0.5°C [145] and rectal temperature of horses (E. ferus caballus) by 1°C [139]. Rectal temperature fell similarly in starved goats and sheep [146].…”
Section: Physiological Adjustmentsmentioning
confidence: 99%
“…Pronounced seasonal fluctuations in metabolic rate, as indexed by heart rate, have been observed in moose, Alpine ibex (Capra ibex ibex), red deer (Cervus elaphus) and horses (Equus ferus caballus and E. ferus przewalskii) in winter [68,[136][137][138][139], when the animals have to cope with low quality and difficult to access (e.g., if covered with snow) plant material. In desert environments, food availability closely follows precipitation, so large desert mammals typically experience insufficient food not during winter, but during summer, at a time when they are not exposed to cold stress.…”
Section: Physiological Adjustmentsmentioning
confidence: 99%
See 1 more Smart Citation